Daniel Chester French papers - French, Daniel Chester, 1850-1931.; Cresson, Margaret French, 1889-1973.; Cresson, Margaret French, 1889-1973.
Correspondence, writings, financial records, scrapbooks, newspaper clippings, photographs, and other papers relating chiefly to French's career as an artist and sculptor and to the French family. Subjects include his sculpture of Abraham Lincoln for the Lincoln Memorial, Washington, D.C., and the artistic milieu of the period. Papers of his daughter, Margaret French Cresson, reflect her career as a sculptress, author, and lecturer as well as her service with many cultural organizations. Includes drafts and proof of her book Journey into Fame; The Life of Daniel Chester French (1947). Other French family members represented include Sarah French Bartlette, W.P. Cresson, Amos Tuck French, Henry F. French, and Mary Adams French French.
Correspondents include Henry Bacon, Gutzon Borglum, Robert M. Bush, W.W. Harts, Margaret F. Jameson, Hermon Atkins MacNeil, Charles Moore, George Foster Peabody, Edward Robinson, Lorado Taft, and Adolf A. Weinman.
Microfilm edition of the collection (containers 1-44; 73-89) with the exception of the Margaret French Cresson papers available
Microfilm produced from originals in the Manuscript Division.
Library of Congress Prints and Photographs Division.
Sculptor and artist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bacon, Henry, -- 1866-1924 -- Correspondence; Bartlette, Sarah French; Borglum, Gutzon, -- 1867-1941 -- Correspondence; Bush, Robert M. -- Correspondence; Cresson, W. P. -- 1873-1932.; French, Amos Tuck, -- 1863-1941.; French, Henry F. -- 1813-1885.; French, Mary Adams French, -- 1859-1939.; Harts, W. W. -- 1866-1961 -- Correspondence; Jameson, Margaret F. -- Correspondence; Lincoln, Abraham, -- 1809-1865 -- Statues -- Washington (D.C.); MacNeil, Hermon Atkins, -- 1866-1947 -- Correspondence; Moore, Charles, -- 1855-1942 -- Correspondence; Peabody, George Foster, -- 1852-1938 -- Correspondence; Robinson, Edward, -- 1858-1931 -- Correspondence; Taft, Lorado, -- 1860-1936 -- Correspondence; Weinman, Adolph A. -- 1870-1952 -- Correspondence; French family; Arts; Lincoln Memorial (Washington, D.C.); Memorials -- Washington (D.C.); Sculpture; Statues -- Washington (D.C.); Artists; Sculptors